Relationship between perceived enjoyment, exercise commitment and behavioral intention among adolescents participating in “School Sport Club” - Joung, Kihong; Jeon, Wonjae; Kwon, Goomyeung (Frontiers in Medicine, 2024)
This study aimed to examine ways to improve the quality of physical activity (PA) to address social problems related to obesity and being overweight among adolescents, through an educational approach. In this regard, the current study identified associations between factors that lead to sustained PA participation among middle school students participating in school sports club activities, and derived academic implications that can be incorporated into future school education programs. The researchers explored the relationship between perceived enjoyment, exercise commitment, and behavioral intention in middle school sports club participants. The subjects of the study were selected as middle school students who had participated in school sports clubs for more than 6 months. Using convenience sampling, 350 datasets were collected from middle school students living in metropolitan cities in South Korea. Finally, 336 datasets were used for the final analysis after eliminating 14 questionnaires that were judged to be incorrectly indicated or incomplete. Frequency analysis, exploratory factor analysis, and reliability verification (Cronbach's α) were conducted. The findings were as follows: first, among the sub-factors of perceived enjoyment, the following were found to have a positive relationship with cognitive commitment: daily escape (β=0.259), competitive victory (β=0.228), interpersonal relationships (β=0.204), and physical fitness (β=0.119). Furthermore, among the sub-factors of perceived fun, physical health (β=0.330), daily escape (β=0.205), interpersonal relationships (β=0.307), and competitive victory (β=0.228) had positive relationships with behavioral commitment. Second, among the sub-factors of perceived enjoyment, physical health (β=0.423), interpersonal relations (β=0.139), and daily escape Relationship between Perceived enjoyment, Exercise commitment and Behavioral intention among Adolescents participating in "School Sport Club" 2 This is a provisional file, not the final typeset article (β=0.138) were found to have a positive association with behavioral intention. On the other hand, there was no significant relationship between competitive winning (β=0.071) and behavioral intention. Third, behavioral commitment (β=0.237) and cognitive commitment (β=0.183) were confirmed to have a significant positive relationship with behavioral intention. These findings highlight that middle school students' perceived enjoyment from participating in school sports clubs is a positive factor leading to increased immersion in sports activities and a sufficient basis for continuing sports activities.